Optimizing the energy bandwidth for transmission full‐field X‐ray microscopy experiments. (13th December 2021) - Storm, Malte; Döring, Florian; Marathe, Shashidhara; Cipiccia, Silvia; David, Christian; Rau, Christoph
Abstract : Results are presented for full‐field transmission X‐ray microscopy (TXM) acquired at different energy bandwidths; the trade‐offs in achievable resolution and acquisition speed are discussed. Abstract : Full‐field transmission X‐ray microscopy (TXM) is a very potent high‐resolution X‐ray imaging technique. However, it is challenging to achieve fast acquisitions because of the limited efficiency of the optics. Using a broader energy bandwidth, for example using a multilayer monochromator, directly increases the flux in the experiment. The advantage of more counts needs to be weighed against a deterioration in achievable resolution because focusing optics show chromatic aberrations. This study presents theoretical considerations of how much the resolution is affected by an increase in bandwidth as well as measurements at different energy bandwidths (Δ E / E = 0.013%, 0.27%, 0.63%) and the impact on achievable resolution. It is shown that using a multilayer monochromator instead of a classical silicon double‐crystal monochromator can increase the flux by an order of magnitude with only a limited effect on the resolution.